A Self‐Assembled Binary Protein Model Explains High‐Performance Salivary Lubrication from Macro to Nanoscale. Issue 1 (20th November 2019) - Xu, Feng; Liamas, Evangelos; Bryant, Michael; Adedeji, Abimbola Feyisara; Andablo‐Reyes, Efren; Castronovo, Matteo; Ettelaie, Rammile; Charpentier, Thibaut V. J.; Sarkar, Anwesha
Abstract: Salivary pellicle, a spontaneously formed, intricate architecture in the human oral cavity, is a high‐performance bio‐lubricant that coats and protects biological surfaces with varying elastic modulus against frictional damage. Although salivary lubrication underpins the fundamentals of human feeding and speech, the peculiar molecular mechanism behind such lubrication properties remains elusive. For the first time, this work demonstrates a binary model comprised of salivary proteins, mucin, and lactoferrin (LF), forming an electrostatically driven, multilayered self‐assembly that exhibits a lubrication behavior closely resembling that of human saliva, from macro to nanoscale. The multiscale tribological analysis with applied forces ranging from 1 N to 1 nN, supported by real‐time self‐assembly monitoring on hydrophilic and hydrophobic substrates differentially resolves the distinct roles played by the salivary proteins of this proposed lubricating model. Evidences reveal that hydrated mucin controls the macromolecular viscous lubrication entrapping water molecules in the mucinous network and LF acts as a "molecular glue" between mucin–mucin and mucin–surface, latter aiding boundary lubrication. This study puts forward an unprecedented molecular model that explains the synergistic lubrication by salivary components. These results can aid into the design routes for synthesizing highly efficacious nature‐inspired aqueous lubricants for future biomedical applications and nutritional technologies. Abstract : For the first time, a self‐assembled binary structural model of salivary proteins uncovers the peculiar molecular mechanism behind the outstanding lubrication performance of human saliva across scales, clearly pinpointing the synergistic relevance of negatively charged mucin and positively charged nonmucinous proteins. Facile design rules from this study can be employed for robust nature‐inspired aqueous lubricant fabrication.